Inovasi Pembelajaran IPA SD dengan Pemanfaatan Media KIT Alat Sederhana yang Berasal dari Lingkungan Sekitar Untuk Meningkatkan Kompetensi dan Kreativitas Siswa - Khoirun Naimah (PT FORMOSA CENDEKIA GLOBAL, 2022)
Natural Science is one of the lessons taught from elementary school to college, but until now many students who do not like science, students consider science as difficult and unpleasant material. In fact, based on the results of IPA learning observations at SDN 1 Bendosari obtained information that most IPA learning on sound properties still use conventional learning with lecture methods, focusing more on material mastery and providing less experience of practical skills. Thus, in order to learn science more interesting and delight students, teachers need to make innovations in learning. The research study is focused on the innovation of SD IPA learning with the use of simple tool media kits derived from the surrounding environment to improve competence and creativity. This research is qualitative research with a descriptive approach. Data is obtained through observations, in-depth interviews to principals and teachers at SDN 1 Bendosari, data collection of observations, interviews, and documentation.